(3GdeKdK aj GddZIs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3MQa GdGda HGH GdeKdK GdeJab GdeYGfi hgh JSYI CMQa s
(3BNQgG (B:s
(3jfJgi HPcQ GdCdaGX GdJi dGfXGFQ dgG HHGH eG jcJH HGdSjf eeG dGfXjQ dg ai GdUGO Hbhdg (B: (3heGA SdSHjd YPH hGdSdSHjd Yjf ai GdLfI bO PcQfG CYRc Gddg ef gPG GdfhY GdPi bUfG Edjg eG ajg caGjI hced GdcJGH s
(3GdeNWhW eYg eNWhW GdaQb Hjf GdMQha GdNeSI (B]s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI fGbUI GdChd s
Keywords: (3GddZIs